Áreas marinhas protegidas da América do Sul sob ameaça do tributilestanho (TBT) - Machado, Fabiano Bender [UNIFESP] (2017)
The tributyltin (TBT) is a compound used in marine antifouling systems since the 1960’s. It is a hazardous chemical presenting high environmental toxicity and responsible for inducing imposex in more than 250 gastropod species molluscs. Banned worldwide in 2008, but is still used in small vessels and its effects have been detected over the last years in Marine Protected Areas (MPA). The present study evaluated, based on available literature data and in a case study if MPAs from South American coast are under threat of TBT contamination.To do so, a georeferenced database was constructed with data published in 55 scientific review papers (published between 2002 and 2017) that evaluated this type of contamination in the coastal zones of South America. These data were overlaid with data from the World Database Protected Areas (WDPA), showing TBT contamination and imposex incidence in 54 marine MPAs between the years 2002 and 2017. Among these areas, there are MPAs from different categories located in Argentina, Brazil, Chile, Ecuador and Venezuela. These observations indicate a worrying situation regarding the protection of the South American protected areas against the impacts caused by environmental inputs of hazardous chemical substances. In the second phase of the study, a case study aimed at assessing the impacts of TBT was performed through the collection and analysis of the presence of imposex in individuals of Stramonita brasiliensis. In this study, 16 out of 17 sampled sites evaluated inside Environmental Protected Areas from north and central coast of São Paulo state presented evidence of imposex incidence. Although the imposex levels detected in these areas have been low, they are indicative of local contamination by TBT, probably used in naval antifouling systems of small vessels. Considering that MPAs are designed to protect natural resources, the results of the present study indicate that the objectives of South American MPAs may be compromised. Therefore, changes in legislation regulating the use of TBT in ships, regulation of navigation in MPAs, and a policy that considers the chemical risks to which MPAs are exposed should contribute to preventing and / or reducing such threat.